Assessing Postural Risks in the Building Construction Sector: A Case Study in Bangladesh - Md. Sumon Rahman; Md. Kutub Uddin; Mohammad Iqbal (Occupational Health and Safety Society of Nepal, 2024)
Introduction: Among the different parts of the construction sectors, the building sector needs more workers for materials handling because of the absence of proper infrastructural facilities. Work-related musculoskeletal disorders (WRMSDs) can occur due to awkward body postures and repetitive and long-term contact of body parts with this activity. The main aim of this study was to evaluate the body posture risk levels among building construction workers in Bangladesh. Methods:  This study was conducted using an ergonomic technique called Rapid Entire Body Assessment (REBA) to analyze the body postures of the building construction workers and assess the risk level of WRMSDs. This research examined primary construction tasks such as concrete laying, lifting and carrying materials, bricklaying, plastering, and sand mixing. Results: The results revealed that the selected tasks' average REBA score was 9.50. It indicates that the postural risk level is high and that certain workers worked in poor postures, putting them at risk of developing WRMSDs. Traditional working methods, as well as non-ergonomic tools and equipment, are to blame for these issues. Conclusion: The findings of this study showed that the postural risk level for building construction workers is alarming. This problem may mitigate by the redesign or change of working methods and equipment in an ergonomic way. Working in proper postures may also minimize the risk of WRMSDs.